THE ESTABLISHMENT OF HOLDING COMPANY FOR INDONESIAN STATE-OWNED ENTERPRISES (OPTION OR REQUIREMENT) - Rolib Sitorus (Universitas Muhammadiyah Ponorogo, 2018)
Sometimes, a big company that has developed business broadly needs to be divided based on their business categories. However, it will be effective if the divided, independent companies, hereby called as subsidiaries, are controlled and managed by certain central leader. Therefore, those subsidiaries and other former companies with the same owner or correlated by particular relation are managed and owned by an independent parent company. This parent company is what is defined as holding company. Holding company or parent company is a company that aims to own the shares of one or more other companies and to control them. Usually, a holding company owns many subsidiaries focusing in different field of business. Generally, there are three procedures available in the process of establishing a holding company. They are (1) residue procedure, (2) complete procedure, and (3) structured procedure.